Learning to Write Procedural Texts on Mathematics Topic Using Mutiple Strategies Through Google Form-Based Learning Materials - Zazuli, M. Zahir; Hermandra; Mustafa, M. Nur (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study aims to explore the learning process of writing skills of mathematical topic procedure texts using modeling techniques and test techniques through special teaching materials, learning outcomes of writing skills of mathematical topic procedure texts using modeling techniques and test techniques. The population of the study was students of grade 7 of MTs Negeri 1 Pekanbaru who took part in the learning process of writing skills of mathematical topic procedures using modeling techniques and test techniques through special teaching materials. They numbered 61 students divided into two parallel classes; 29 students of grade 7A and 32 students of grade 7B. The sample was determined as many as 53 students divided into 26 students of grade 7A and 27 students of grade 7B. Each sample member was drawn randomly. Research instruments: simple teaching materials containing models of mathematical topic procedure texts, lesson plans, observation guidelines, checklists, test devices for writing skills of mathematical topic procedures. Learning process data were analyzed using a thematic approach. Learning outcome data were analyzed using parametric inferential statistical procedures. Research results: the learning process involved 3 initial activities, 19 core activities, and 2 final activities. learning outcomes reached the target of 85.00.